Antibody to Hepatitis G Mrus after a Vapour-Heated Factor Vlll Goncentrate - Mannucci, P M; Zanetti, A R; Colombo, M; Chistolini, A; De Biasi, R; Musso, R; Tamponi, G; the Study Group of the Fondazione deii–Emofilia (Thrombosis and Haemostasis, 1990)
To evaluate whether or not clotting factor concentrates exposed to virucidal procedures transmitted hepatitis C, sera obtained in 1984–1986 from 27 previously untreated hemophiliacs infused with a vapour-heated factor VIII concentrate were tested retrospectively for the antibody to the hepatitis C virus (anti- HCV). A 2-year-old hemophiliac, negative for anti-HCV before administration of concentrate, seroconverted at week 12 and remained anti-HCV positive thereafter. Both his parents were anti-HCV negative and he had no other household contact. The patient had also become HBsAg positive at week 8 and had at the same time a marked elevation of alanine aminotransferase. His double infection with the hepatitis B and C viruses indicates that hot vapour was not completely effective in inactivating these viruses.